The Significant Structure Theory Applied to Amorphous and Crystalline Polyethylene - Ma, Shao-Mu (1974)
The significant structure theory of liquids has been applied to amorphous and crystalline polyethylene. In this theory the amorphous state, like liquids in general, is assumed to have solid-like structure, gaslike structure, and positional degeneracy which arises from the motion of kinetic segments and from the libration of CH(2) units. This concept leads to a partition function giving the Helmholtz free energy in terms of volume, temperature, and composition. Thermodynamic and transport properties are calculated for amorphous polyethylene. The thermodynamic properties are also calculated for the crystalline solid. The calculated results are in reasonable agreement with the experimental values. No such detailed calculations of polymer properties from a partition function, depending on both volume and temperature, have been previously attempted.